Allele and haplotype frequencies of 19 X-STRs in the Kyrgyz and Han populations from Kizilsu Prefecture. (May 2019) - Li, Ye; Li, Xiong; Chen, Wanying; Fan, Yujiang; Xie, Mingkun; Wu, Jin
Highlights: Constructing a database of 19 X-STR loci in the Kyrgyz and Han populations. Providing insight into the population history using various biostatistics methods. LD analysis suggested that it is necessary to establish the ethnic specific databases.